Karakterisasi Edible Film Berbasis Porang Glukomanan Inkorporasi Ekstrak Bunga Telang (Clitoria ternatea) - Nauli, Asti P; Harefa, Kurnia S E; Sihombing, Tamara A; Simanjuntak, Parto (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
Biopolymer-based edible films offer an eco-friendly alternative to synthetic plastics for packaging. This study investigated the effect of different concentrations of butterfly pea flower (Clitoria ternatea extract on the physical, mechanical, and antioxidant properties of porang glucomannan-based edible films. The films consisted of a control without extract (EF1) and treatments containing 10% (EF2) and 20% (EF3) butterfly pea extract. Analyses included measurements of thickness, tensile strength, and DPPH radical scavenging activity. The results showed that the film thickness was highest in EF1 (0.164 mm), lower in EF2 (0.157 mm), and lowest in EF3 (0.148 mm). For tensile strength, EF1 exhibited the highest value (18.32 MPa), followed by EF3 (15.61 MPa), while EF2 showed the lowest value (9.79 MPa). Antioxidant activity, expressed by IC₅₀, was highest (least active in EF1 (24,631.20 mg/L, decreased in EF2 (3,736.68 mg/L, and was lowest (most active in EF3 (2,668.82 mg/L. These results indicate that higher concentrations of butterfly pea extract reduce thickness and IC₅₀ while exerting variable effects on tensile strength. Overall, EF3 (20% extract provided the best balance between mechanical and bioactive properties, supporting its potential as an active natural biopolymer packaging material.